2016
DOI: 10.1093/mnras/stw2253
|View full text |Cite
|
Sign up to set email alerts
|

Dead or Alive? Long-term evolution of SN 2015bh (SNhunt275)

Abstract: Supernova (SN) 2015bh (or SNhunt275) was discovered in NGC 2770 on 2015 February with an absolute magnitude of M r ∼ −13.4 mag, and was initially classified as a SN impostor. Here we present the photometric and spectroscopic evolution of SN 2015bh from discovery to late phases (∼ 1 yr after). In addition, we inspect archival images of the host galaxy up to ∼ 21 yr before discovery, finding a burst ∼ 1 yr before discovery, and further signatures of stellar instability until late 2014. Later on, the luminosity o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 88 publications
5
92
2
Order By: Relevance
“…(ii) The duration of Event A appears to vary for the five objects, lasting from a few weeks in LSQ13zm (Tartaglia et al 2016) to over 3 months, and with a bumpy rise in SN 2016bdu and SN 2015bh (Elias-Rosa et al 2016;Thöne et al 2017). The absolute magnitudes of the A events are between M R/r = −14.5 and −15.3 mag.…”
Section: Photometrymentioning
confidence: 98%
See 3 more Smart Citations
“…(ii) The duration of Event A appears to vary for the five objects, lasting from a few weeks in LSQ13zm (Tartaglia et al 2016) to over 3 months, and with a bumpy rise in SN 2016bdu and SN 2015bh (Elias-Rosa et al 2016;Thöne et al 2017). The absolute magnitudes of the A events are between M R/r = −14.5 and −15.3 mag.…”
Section: Photometrymentioning
confidence: 98%
“…The duration and the luminosity of the two events are comparable in all SN 2009ip-like objects, which also show remarkable similarity in their spectral evolution (at least, at phases when spectroscopic observations exist; see Section 2.3). This observed homogeneity is even more puzzling for progenitors possessing strongly asymmetric circumstellar environments (Levesque et al 2014;Mauerhan et al 2014;Elias-Rosa et al 2016;Thöne et al 2017), whose orientation with respect to the line of sight is expected to play an important role. The striking spectroscopic and photometric similarities of the five SN 2009ip-like transients suggest that these objects very likely arise from similar stars (or stellar systems) and may have undergone a comparable fate.…”
Section: E Ru P T I O N S M E R G E R S O R S N E X P L O S I O Nmentioning
confidence: 99%
See 2 more Smart Citations
“…This includes SN 1998S (Leonard et al 2000), SN 1997eg (Hoffman et al 2008), SN 2009ip (Levesque et al 2014Mauerhan et al 2014;Smith, Mauerhan & Prieto 2014), SN 2010jl (Andrews et al 2011;Patat et al 2011;Smith et al 2012;Chandra et al 2015;Katsuda et al 2016), PTF11iqb and SN 2015bh (Elias-Rosa et al 2016). Recently, Mauerhan et al (2017) suggested that the IIP/L SN2013ej SN likely had an equatorial enhanced CSM close to edge on based on spectropolarimetry.…”
Section: The Multipeaked Shape Of H αmentioning
confidence: 99%